Technique of anatomic single Bundle ACL reconstruction with Peroneus Longus Autograft (Journal of Pharmaceutical Negative Results, 2023)
Anterior Cruciate Ligament (ACL) reconstruction is a common ligament reconstruction to restore functional knee stability. However, the site of graft harvesting is vulnerable to have donor site complications of management occurs in a number of cases, in this review we aimed to evaluate treatment of anterior cruciate ligament by reconstructed with peroneus longs autograft.